2014
DOI: 10.3390/ijms151119406
|View full text |Cite
|
Sign up to set email alerts
|

Association Study Identifying a New Susceptibility Gene (AUTS2) for Schizophrenia

Abstract: Schizophrenia (SCZ) is a severe and debilitating mental disorder, and the specific genetic factors that underlie the risk for SCZ remain elusive. The autism susceptibility candidate 2 (AUTS2) gene has been reported to be associated with autism, suicide, alcohol consumption, and heroin dependence. We hypothesized that AUTS2 might be associated with SCZ. In the present study, three polymorphisms (rs6943555, rs7459368, and rs9886351) in the AUTS2 gene were genotyped in 410 patients with SCZ and 435 controls using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 40 publications
1
31
1
Order By: Relevance
“…In addition, 24 exonic microdeletions were identified in the AUTS2 gene in individuals with various psychiatric disorders (Beunders et al, 2013). Moreover, very recent studies suggested that this gene is also associated with schizophrenia (Zhang et al, 2014;McCarthy et al, 2014). The wide spectrum of phenotypes observed in patients with AUTS2 mutations suggests that this gene is not associated with a specific type of ASD but with a broader range of psychiatric disorders, thus highlighting AUTS2 as a current gene of interest .…”
Section: Introductionmentioning
confidence: 96%
“…In addition, 24 exonic microdeletions were identified in the AUTS2 gene in individuals with various psychiatric disorders (Beunders et al, 2013). Moreover, very recent studies suggested that this gene is also associated with schizophrenia (Zhang et al, 2014;McCarthy et al, 2014). The wide spectrum of phenotypes observed in patients with AUTS2 mutations suggests that this gene is not associated with a specific type of ASD but with a broader range of psychiatric disorders, thus highlighting AUTS2 as a current gene of interest .…”
Section: Introductionmentioning
confidence: 96%
“…Autism susceptibility candidate 2 (AUTS2) (also termed "activator of transcription and developmental regulator") located on human chromosome 7q11.22 has been initially identified as a possible ASD risk gene in a study that reported a de novo balanced translocation in monozygotic twin patients with ASDs (Sultana et al, 2002). Thereafter, structural variants that disrupt the AUTS2 locus have been identified in the patients with not only autism, but also other neuropathological conditions including intellectual disabilities (IDs), schizophrenia, attention deficit hyperactivity disorder (ADHD), dyslexia and epilepsy as well as brain malformation and craniofacial abnormalities (Amarillo et al, 2014;Bakkaloglu et al, 2008;Ben-David et al, 2011;Beunders et al, 2013;Elia et al, 2010;Hori and Hoshino, 2017;Jolley et al, 2013;Kalscheuer et al, 2007;Talkowski et al, 2012;Zhang et al, 2014). In addition, AUTS2 has been recently implicated as a potential gene in human-specific evolution .…”
Section: [Introduction]mentioning
confidence: 99%
“…In these genes, only TAF13 and SETD1A were suggested as top genes in previous study (Fromer, et al, 2012;Nguyen, et al, 2017). In addition, AUTS2 (PP>0.8) was reported as a SCZ genes from a common variant based study (Zhang, et al, 2014). Using expression data, multiple genes of these genes were expressed in prenatal stages, but the signals were as not strong as those of CHD ( Figure S6).…”
Section: Sczmentioning
confidence: 86%